A tool for curricular evaluation of the management function of Medicine career - Niurka Taureaux Díaz; Eva Miralles Aguilera; Agustín G. Vicedo Tomey; Georgia Díaz-Perera Fernández; Simón Sierra Figueredo; Marta Pernas Gómez; Miguel Ángel Blanco Aspiazu; Julieta Sonia Damiani Cavero; Leticia Galvéz Gómez; Javier Agustín Molina López; José Díaz Novás; Vladimir Curbelo Serrano (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Current medical training in Cuba responds to the health needs of the population of our country and others worldwide. The Teaching and Research Department belonging to the Ministry of Public Health created a research group, which designed the project "Medicine Curriculum Effectiveness". One of the partial curriculum assessments evaluates the correspondence between the professional model declared for the five functions described in the curriculum and professional training. One of the five functions described in the model is the management function. Objective: To design a tool to assess the correspondence between the management function declared and modeled in the curriculum and the actual results showed by professionalist on training. Material and Methods: An investigation of technological development was performed in three stages: First: design an assessment instrument; Second: implementation of the survey and of theoretical - practical exercise; Third: valuation of the instrument.  Results: The designed instrument demonstrated that, with the current educational curriculum, management function is fulfilled in a 77.07%. All the teachers and mostly of students disclosed correctly, focusing their opinions on the required aspects for validation. Conclusions: Was designed a tool for assessing the correspondence between the management function declared and modeled in the curriculum and the actual results showed by the training professionalist. The applied validation actions support the instrument's tenability in terms of their operativeness and content. Keywords: Management function, assessment instrument, validation, career, Medicine, design.